Avaliação da qualidade da videolaringoscopia com capa de câmera odontológica na presença de lesões de cobertura de prega vocal - Bozo, Marlon Kleber Wutzow (2018)
The examination of the larynx is one of the steps in the otorhinolaryngological consultation, and can be performed with the aid of instruments, such as the rigid laryngoscope with the chip camera provides a scan of the obtained image, making videolaryngoscopy an effective solution for the diagnosis of laryngeal lesions. Proper reprocessing of endoscopes is imperative to prevent contamination of the device and subsequent risks of cross-contamination and infection of patients. The endoscopic sheaths that cover the laryngoscope are recommended to prevent cross-contamination, but they may hamper visualization, the most important tool in the diagnostic approach to laryngeal disease. It is believed that the use of the Disposable Intraoral Oral Protection Case (CPCIO) can act as a mechanical barrier and prevent contact of the laryngoscope with a patient's mucosa, in the manner and contact occurring only between a CPCIO and the microorganisms of the flora of the patient. The aim of this study was to investigate the maintenance of image quality in traditional videolaryngoscopy examinations, with and without a disposable intraoral camera protection cover, for the execution of the reports of patients with laryngeal lesions. This is a cross-sectional, quantitative and qualitative, and accurate, study on videolaryngoscopy (VDL) images with a disposable intraocular camera protective cap (CPCIO). The images were captured by rigid videolaryngoscopy of the type of digital camera chip on the tip (optometrist) of the Otorhinolaryngology Clinic of the Red Cross Hospital - Paraná, in Curitiba-PR. The participants of the present investigation were some patients of the clinic mentioned above who presented a visible lesion of mucous cover of vocal folds in videolaryngoscopy and who fullfield inclusion and exclusion criteria. The images were collected through videolaryngoscopy with videolaryngoscope with a chip camera on the Scott 960® tip and in two steps: 1) Videolaryngoscopy with the protective cover of the disposable intraoral camera, and 2) Videolaryngoscopy without a protection layer of the disposable intraoral camera. After obtaining the images, the laryngoscope was submitted to processing and disinfection according to the Technical Protocol of the Brazilian Association of Otorhinolaryngology between one participant and another. The images obtained were randomly distributed, and patient identification will be coded. After editing images and videos were randomly presented to each participating professional to evaluate the image quality. The data obtained from the professionals' answers are analyzed by means of descriptive statistics and the application of parametric and non-parametric variables association tests for the relationship between the difference in the reports and the use of CPD.